Pengaruh Financial Literacy, Locus of Control, Life Style, dan Gender terhadap Financial Management Behavior Mahasiswa Universitas Negeri Surabaya - Sari, Novita (Jurnal Ilmu Manajemen, 2021)
Financial management behavior is essential to have for everyone to achieve their financial goals. This research aimed to determine financial literacy, locus of control, lifestyle, and gender on financial management behavior. Respondent to this research is the students of Universitas Negeri Surabaya. The sample number is 100 respondents with random sampling obtained from online questionnaires—the research method uses a quantitative approach. Data were analyzed using multiple linear regression and processed using SPSS 23. The result of this research is that the variables of financial literacy, locus of control, lifestyle, and gender positively affect personal financial planning. Universitas Negeri Surabaya, especially the student career development section and the Financial Services Authority (OJK), can use this study's results to educate millennials about the importance of managing and planning finances properly.